Hyers-Ulam Stability to Linear Nonhomogeneous Quaternion-Valued Matrix Difference Equations via Complex Representation - Wang, Jiangnan; Wang, JinRong; Liu, Rui (Qualitative theory of dynamical systems, 2024)
This paper focuses on the Hyers-Ulam stability to linear nonhomogeneous quaternion-valued matrix difference equations via complex representation. Then one can transfer the second-order and higher-order linear nonhomogeneous quaternion-valued difference equations into the first-order linear nonhomogeneous quaternion-valued matrix difference equations to obtain their Hyers-Ulam stability results. Finally, two examples are given to illustrate the theoretical results.